PENGARUH KOMITMEN ORGANISASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN - AGUS WIBOWO, RONNY (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: The purpose of this research is to partially and simultaneously know whether organization’s commitment and work stress influence the employees’ performance of PT. Lion Superindo Cabang Citraland Surabaya. The samples used in this research are 43 employees of PT. Lion Superindo Cabang Citraland Surabaya, while in analyzing the data the writer used multiple linear regression method. The result found that at the same time (simultaneously) organization’s commitment (X1) and work stress (X2) influence employees’ performance (Y), and partially those two variables, organization’s commitment and work stress, influence employees’ performance. The dominant free variable which influences employees’ performance in PT. Lion Superindo Cabang Citraland Surabaya is work stress. Keywords: organization’s commitment, work stress, employees’ performance.